Characterization of the labor market of dietitian nutritionists in Valle del Cauca, Colombia - Berdugo-Alomias, Brigitt Katty; Rincon-Quintero, Erleny; Piñeros, Alba; Perdigón, Valentina (Universidad y Salud, 2026)
Introduction: The working conditions and academic training of dietitian-nutritionists have not been extensively studied. Understanding their professional profile and career trajectories is essential to enhance employability and meet current labor market demands. Objective: This study aimed to characterize the labor and occupational market of dietitian-nutritionists in Valle del Cauca, Colombia. Materials and methods: A descriptive, cross-sectional study was conducted. An online survey was administered to 145 dietitian-nutritionists using non-probability convenience sampling. The instrument included 39 questions covering sociodemographic, academic, and occupational variables. Descriptive analyses were performed, and the Chi-square test was used to explore associations between categorical variables (p < 0.05). Results: Of those surveyed, 93% were women, with an average age of 32.5 years. Seventy percent had not pursued postgraduate studies, and 41% were working in clinical nutrition. Following the COVID-19 pandemic, 47% adopted a hybrid work model, and 34% reported earnings between 3 and 4 minimum legal monthly wages (MLMW). The highest salaries were reported in public and clinical nutrition. Conclusion: A high rate of labor insertion was observed, with a concentration in the urban private sector and low levels of postgraduate education.